2014
DOI: 10.1089/ten.tec.2013.0203
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Ultrasound-Photoacoustic Imaging of Tissue Engineering Scaffolds and Blood Oxygen Saturation In and Around the Scaffolds

Abstract: Preclinical, noninvasive imaging of tissue engineering polymeric scaffold structure and/or the physiological processes such as blood oxygenation remains a challenge. In vitro or ex vivo, the widely used scaffold characterization modalities such as porosimetry, electron or optical microscopy, and X-ray microcomputed tomography have limitations or disadvantages-some are invasive or destructive, others have limited tissue penetration (few hundred micrometers) and/or show poor contrast under physiological conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…115,116 Linear ultrasound array-based PA imaging is capable of detecting a target at deeper regions than PA microscopy and thus can be applied for a rat model, having been commonly used for tissue regeneration studies. 117,118 For example, it was demonstrated that mesenchymal stem cells labeled with gold nanospheres and delivered within 96 NAM ET AL.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…115,116 Linear ultrasound array-based PA imaging is capable of detecting a target at deeper regions than PA microscopy and thus can be applied for a rat model, having been commonly used for tissue regeneration studies. 117,118 For example, it was demonstrated that mesenchymal stem cells labeled with gold nanospheres and delivered within 96 NAM ET AL.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…106,131 Therefore, fusion of ultrasonically acquired structural data and photoacoustically obtained functional and molecular data can provide synergetic benefits for a variety of applications that require noninvasive monitoring of implanted tissue-engineered constructs. 117,118 Novel dual contrast agents for combined ultrasound and PA imaging have recently been developed by indocyanine green loading to perfluorocarbon nanodroplets. 132 Also, hybrid PA imaging is possible with other optical imaging modalities, such as OCT, by sharing a photon delivery system to complement structural information.…”
Section: Multimodal Imagingmentioning
confidence: 99%
“…Combined ultrasound and photoacoustic images were created by overlaying photoacoustic intensities higher than a user-de ned threshold on the grayscale ultrasound images. The system supports real-time B-mode imaging with spatial resolution down to 40 µm [17].…”
Section: Methods and Materials Combined Photoacoustic And Ultrasounmentioning
confidence: 99%
“…For in vitro applications, however, to date nuclear-based methods are not yet commonly applied. The lateral resolution of nuclear imaging modalities is limited, since most available devices are mainly optimized for human-scale use with a resolution of 1-2 mm [130]. To be able to achieve contrast in nuclear based imaging methods such as single-photon emission computed tomography (SPECT) and positron emission tomography (PET), radioactive agents are required.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…By modulating the US detection frequency after laser irradiation, PAT enables high-resolution imaging of biological structures with strong optical absorption contrasts [212]. Although PAT and PAM are promising imaging methods for in vivo applications, to date just a few researchers have investigated the potential of these methods for the field of tissue engineering [130]. Recently, PAM has been applied to retrieve structural information on tissue engineering constructs in vitro [213,214] and in vivo [122,211].…”
Section: Photoacoustic Tomography (Pat) and Photoacoustic Microscopy mentioning
confidence: 99%